O estado da arte nas pesquisas internacionais de governança em cidades inteligentes - Ferreira, Victor Garcia Figueirôa (2019)
The scientific production of several areas of knowledge has been driven by the theme Smart Cities, mainily for its multidisciplinary characteristics. Thus, urban engineering, as an area that interfaces with other areas of knowledge, becomes essential in the analysis of knowledge and practices under the banner of Smart Cities. Therefore, this work makes a bibliometric and bibliographical analysis on this larger theme, however, with specificity in Governance. Using bibliometrical analysis as an initial methodological tool, this work presents a descriptive and quantitative research of the scientific production in Smart Cities, though it is limited to the publications in english-language journals, within the intersection of 1997 and 2017, represented by the scientific articles indexed in the Scopus database. 1886 articles published in renowned journals in that area and 136 in governance within Smart Cities were analyzed, which made possible to obtain the number of articles published per year. The results exhibit the growing interest in this field, demonstrated both by the increase in scientific production throughout the period, by the analysis performed through non-linear regression models and also by the correlation to important world events such as Rio +20 and 2030 Agenda. Subsequently, using the data obtained in the quantitative phase, a qualitative analysis of the main articles of the large area of Smart Cities and of governance in this context was developed. Therefore, this study provides a global perspective of the scientific literature on Smart Cities, through original analyzes in the area.